Tutoring insertion in the undergraduate nursing course - Evanilda Souza de Santana Carvalho; Norma Carapiá Fagundes (Rev Rene)
This research discusses the insertion of tutoring in curriculum training programs in the nursing course. Objectives: to understand the different views concerning tutoring among nurses who carry out this task in Health Care Units; identify advances and difficulties nurses have had during tutoring; identify demands for the preceptors’ permanent education and contribute to the institutionalization of tutoring in the nursing under graduation courses. Results and discussion: It was evidenced that nurses were not prepared to do their tasks, there is little commitment by the university regarding the preceptor qualification and along apprenticeship; little involvement by preceptors to plan the activities; discontinuation of actions caused by the rotation of nurses on duty; not enough availability from professionals and through the distance of the university after the school year. Final considerations: the results reinforce the necessity of a well-established and planned policy between the university and the health services for the training program.